Analisis Pertanggungjawaban Pencemaran Lingkungan Akibat Tumpahan Minyak (Studi Kasus: Kebocoran Pipa Minyak di Teluk Balikpapan) - Fatmawaty, Dewi (Bumi Lestari; Vol 20 No 1 (2020)DO - 10.24843/blje.2020.v20.i01.p03, 2020)
Environmental pollution in marine waters has a very broad impact on all life both at sea and on land. The oil spill not only affects the ecosystem, but also affects the health and economy of the surrounding community. This study aims to determine the extent of efforts to resolve cases of marine pollution due to oil spills in Balikpapan Bay. This research method uses this type of research is a normative juridical approach method which is done by examining library materials or secondary data as a basis for research by searching the regulations and literature relating to research problems. Qualitative analysis, which uses literature as a source of research data. Liability for oil spill cases in Balikpapan Bay can be carried out through civil lawsuits against parties related to pollution. In addition, it is important to immediately make arrangements regarding RZWP3K to realize harmony and synergy in the utilization of coastal areas and small islands between regional governments and related sectors.